(untitled) (Biocenosis, 2022)
Water management in industries can have a positive influence on their earning profits and enhance access to investment and green funds, as well. However, considering agricultural expansion, the exponential growth of the population, and climate change, water has become a global concern. The industrial sector is often accused of being an agent of pressure for interfering both locally and systemically on water resources. Therefore, companies must develop strategies oriented to the efficient use of water, as well as to the generation of indicators to address future challenges. This paper reexamines the concepts of water footprint and the most common approaches to water management. It reviews elements of the volumetric approach of the Water Footprint Network (WFN) as well as the ISO 14046 standard as recommended methodology to generate impact indicators for different goods and services. A review of good environmental practices, cleaner production strategies and successful cases in the reduction of water consumption in industries is included in this work, in which the authors highlight the role of industries in the conservation of water resources and ecosystems. The paper also reflects on the importance of water management for sustainable development and the usefulness of water management indicators for strategic decision-making practices in companies. A final remark is made on social corporate responsibility regarding the management of water to promote competitivity.